Enhancing professional communication: A study of English business correspondence in international business contexts - Wajdi, Majid; Dizon Jr, Rodolfo P.; Sahoo, Parshuram; Ghafar, Zanyar Nathir; Hasan, Md. Kamrul (Yayasan Mitra Persada Nusantara, 2025)
In the era of globalization and rapid international trade, business correspondence has emerged as a crucial tool for effective cross-cultural communication and professional success. This study aims to examine the role of English business correspondence in international business management, focusing on its linguistic features, communication strategies, and the challenges faced by non-native speakers. The research employs a qualitative descriptive method supported by content analysis of real-life business letters, emails, and memos collected from multinational companies. In addition, interviews with professionals and language instructors were conducted to identify the key skills required for writing effective business correspondence. The analysis reveals that clarity, conciseness, and formal tone are vital elements that define successful business writing. Moreover, intercultural awareness and pragmatic competence significantly impact the tone and appropriateness of communication in diverse business environments. Findings also indicate that learners of English for Business Purposes (EBP) often struggle with vocabulary selection, cultural politeness norms, and organizational structure in written messages. The study concludes that mastering English business correspondence requires a combination of language proficiency, cultural sensitivity, and real-world practice. It recommends incorporating authentic business writing samples into teaching materials, developing learner awareness of formal language structures, and providing consistent feedback. These findings are particularly useful for English educators, corporate trainers, and international business professionals aiming to enhance communication competence.